2011
DOI: 10.1002/jcb.22959
|View full text |Cite
|
Sign up to set email alerts
|

The effects of estrogen receptors α‐ and β‐specific agonists and antagonists on cell proliferation and energy metabolism in human bone cell line

Abstract: In cultured human osteoblasts estradiol-17β (E2) modulated DNA synthesis, the specific activity of creatine kinase BB (CK), 12 and 15 lipoxygenase (LO) mRNA expression and formation of 12- and 15-hydroxyeicosatetraenoic acid (HETE). We now investigate the response of human bone cell line (SaOS2) to phytoestrogens and estrogen receptors (ER)-specific agonists and antagonists. Treatment of SaSO2 with E2, 2,3-bis (4-hydroxyphenyl)-propionitrile (DPN; ERβ-specific agonist), 4,4',4″-[4-propyl-(1H)-pyrazol-1,3,5-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
(51 reference statements)
0
27
0
1
Order By: Relevance
“…5b). Studies by Somjen et al [42] have shown that E2 and their agonists stimulate ROS production in human osteosarcoma cell line SaOS-2 and this effect is blocked in presence of antiestrogen. Thus, we studied if pretreatment with ICI 182,780 blunts the ability of E2 and Med to inhibit (5) Ovx results in the production of more senescent T cell population that produce more TNF-α thus leading to decreased CD28 expression on CD4 + T cells and enhanced osteoclastogenesis TNF-α-induced ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…5b). Studies by Somjen et al [42] have shown that E2 and their agonists stimulate ROS production in human osteosarcoma cell line SaOS-2 and this effect is blocked in presence of antiestrogen. Thus, we studied if pretreatment with ICI 182,780 blunts the ability of E2 and Med to inhibit (5) Ovx results in the production of more senescent T cell population that produce more TNF-α thus leading to decreased CD28 expression on CD4 + T cells and enhanced osteoclastogenesis TNF-α-induced ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that vitamin D, PTH as well as other hormones including phytoestrogens stimulate DNA and CK as well as LO mRNA and HETE formation [10,11]. We also found that the ER␣ and ER␤ specific agonists have differential effects on all these parameters in the human osteoblastic cell line SaSO 2 [12]. In the present study we analyzed the response of primary human osteoblasts in culture from males or females to the ER␣ agonist PPT and the ER␤ agonist DPN at different parameters, in order to see whether the sex-specificity is retained also using the specific ERs agonist similar to E2 itself.…”
Section: Introductionmentioning
confidence: 60%
“…(a) for 3 days daily for the expression of mRNA for 12LO and 15LO type 1 expression or for estrogen receptor ␣ (ER␣) and estrogen receptor ␤ (ER␤) were determined as previously described [18,19] or; (b) for 1 h with serum-free medium, followed by the addition of vehicle or estrogenic compounds: E2 at 30 nM, DPN at 420 nM and PPT at 390 nM for 10 min and HETE were extracted and assayed as previously described [11,12,20] or; (c) for 24 h with the addition of vehicle or estrogenic compounds: E2 at 30 nM, DPN at 420 nM and PPT at 390 nM for DNA synthesis and for CK specific activity as previously described [12,20]. In these experiments raloxifene (Ral) was used at 3000 nM.…”
Section: Hormonal Treatmentmentioning
confidence: 99%
See 2 more Smart Citations